Oxygenator impact on voriconazole in extracorporeal membrane oxygenation circuits. (September 2020) - Cies, Jeffrey J; Moore, Wayne S; Giliam, Nadji; Low, Tracy; Marino, Daniel; Deacon, Jillian; Enache, Adela; Chopra, Arun
Introduction: To determine the oxygenator impact on alterations of voriconazole in a contemporary neonatal/pediatric (1/4 inch) and adolescent/adult (3/8 inch) extracorporeal membrane oxygenation circuit including the Quadrox-i ® oxygenator. Methods: Simulated closed-loop extracorporeal membrane oxygenation circuits (1/4 and 3/8 inch) were prepared with a Quadrox-i pediatric and Quadrox-i adult oxygenator and blood primed. In addition, 1/4- and 3/8-inch circuits were also prepared without an oxygenator in series. A one-time dose of voriconazole was administered into the circuits, and serial pre- and post-oxygenator concentrations were obtained at 5 minutes, 1, 2, 3, 4, 5, 6, and 24 hour time points. Voriconazole was also maintained in a glass vial and samples were taken from the vial at the same time periods for control purposes to assess for spontaneous drug degradation Results: For the 1/4-inch circuit, there was an approximate mean of 64-67% voriconazole loss with the oxygenator in series and mean of 15-20% voriconazole loss without an oxygenator in series at 24 hours. For the 3/8-inch circuit, there was an approximate mean of 44-51% voriconazole loss with the oxygenator in series and a mean of 8-12% voriconazole loss without an oxygenator in series at 24 hours. The reference voriconazole concentrations remained relatively constant during the entire study period demonstrating that the drug loss in each size of the extracorporeal membrane oxygenation circuit with or without an oxygenator was not a result of spontaneous drug degradation. Conclusion: This ex vivo investigation demonstrated substantial voriconazole loss within an extracorporeal membrane oxygenation circuit with an oxygenator in series with both sizes of the Quadrox-i oxygenator at 24 hours and no significant voriconazole loss in the absence of an oxygenator. Further evaluations with multiple dose in vitro and in vivo investigations are needed before specific voriconazole dosing recommendations can be made for clinical application with extracorporeal membrane oxygenation.